The Quantitative Study on Psychological Distress of patients regarding Hospital Management - Farwa Shafique, Muhammad Fahim Qasim, Asif Kamal, Fatima Amir Khan, Naveed Gani, Mudassar Nazar (Pakistan Journal of Medical & Health Sciences, 2023)
Aim: To examine the effect of elements of emotional distress like diminished quality of life, loss of enjoyment, cognitive changes, embarrassment, psychological trauma and loss of sleep on person’s perception towards illness and how these elements influence self-care management of patients and their adherence to treatment. Methodology: Four number of questionnaires were used to collect data having high reliability and validity from 1000 patients in different areas of Pakistan. Results: The results revealed a significant relationship of psychological distress, illness perception, self care management and adherence to medication. Conclusion: Based on these findings, the greater the psychological distress, the more would be the negative effects on illness perception, self-care management and adherence to medication. Keywords: Psychological distress, illness perception, self-care management and adherence to medication.